2012
DOI: 10.1002/cne.23159
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and full‐field illumination activate D1 and D2‐D5‐type receptors in adult rat retinal ganglion cells

Abstract: Dopamine can regulate signal generation and transmission by activating multiple receptors and signaling cascades, especially in striatum, hippocampus, and cerebral cortex. Dopamine modulates an even larger variety of cellular properties in retina, yet has been reported to do so by only D1 receptor-driven cyclic adenosine monophosphate (cAMP) increases or D2 receptor-driven cAMP decreases. Here, we test the possibility that dopamine operates differently on retinal ganglion cells, because the ganglion cell layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 90 publications
2
39
0
Order By: Relevance
“…FA-based fixatives that do not induce beading have enabled us to visualize dendritic shape, contour, branching, and arborization (Stradleigh et al, 2011), contrast axon calibers (Stradleigh et al, 2011), gauge protein colocalizations (Stradleigh et al, 2011;Partida et al, 2012), and compare the binding of antibodies in dark-and light-adapted retinae (Ogata et al, 2012). Moreover, we have found that replacing NaCl by sucrose suppresses beading even if the fixative pH is shifted to alter fixation speed and efficacy (Berod et al, 1981;Eldred et al, 1983;Stradleigh et al, 2011;Ogata et al, 2012).…”
Section: Applicabilitymentioning
confidence: 90%
See 2 more Smart Citations
“…FA-based fixatives that do not induce beading have enabled us to visualize dendritic shape, contour, branching, and arborization (Stradleigh et al, 2011), contrast axon calibers (Stradleigh et al, 2011), gauge protein colocalizations (Stradleigh et al, 2011;Partida et al, 2012), and compare the binding of antibodies in dark-and light-adapted retinae (Ogata et al, 2012). Moreover, we have found that replacing NaCl by sucrose suppresses beading even if the fixative pH is shifted to alter fixation speed and efficacy (Berod et al, 1981;Eldred et al, 1983;Stradleigh et al, 2011;Ogata et al, 2012).…”
Section: Applicabilitymentioning
confidence: 90%
“…Moreover, we have found that replacing NaCl by sucrose suppresses beading even if the fixative pH is shifted to alter fixation speed and efficacy (Berod et al, 1981;Eldred et al, 1983;Stradleigh et al, 2011;Ogata et al, 2012). The improved preservation of cells by the protectant fixatives we have described here is of particular interest because immunostaining with some antibodies (e.g., monoclonal and polyclonal antibodies directed against D1 dopamine receptors, HCN channel subunits, cAMP, and phosphorylated CaMKII) is compatible with FA-based fixatives (Pow et al, 1995;Hayashida et al, 2009;Stradleigh et al, 2011;Ogata et al, 2012) but not with a variety of other fixatives (e.g., Clarke's fluid, glyoxal, ice cold acetone; unpublished observations). GFP-expressing retinal ganglion cells preserved for 24 hr in standard FA solution (formaldehyde diluted to 4% w/v in phosphate-buffered saline).…”
Section: Applicabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two primary attractions of using formaldehyde are that it is commonly available at reliably high purities and that formaldehyde-fixed retinae have been immunostained with antibodies directed against a wide range of functionally important proteins. The latter include light-sensitive pigments, cGMP-gated ion channels, and associated modulators (Hattar et al, 2002; Haverkamp et al, 2005; Molday et al, 1991; Philp et al, 1987; Seydewitz et al, 2004; Sokolov et al, 2002; Wikler and Rakic, 1990); neurotransmitters, neuromodulators, receptors, synthesizing enzymes, inactivating enzymes, and release-related proteins (Brandon, 1987; Brandstätter et al, 1999; Brecha et al, 1979; Famiglietti and Tumosa, 1987; Guo et al, 2010; Haverkamp et al, 2000; Hendrickson et al, 1985; Keyser et al, 1988; Wagner et al, 1993; Yamada et al, 1980); voltage-gated ion channels, auxiliary subunits, and connexins (Janssen-Bienhold et al, 1998; Klumpp et al, 1995; Morgans, 2001; Müller et al, 2003; Reyes et al, 2000; Stradleigh et al, 2011; Taylor and Morgans, 1998; Van Wart et al, 2007; Wollner and Catterall, 1986); transporters, cytoskeletal elements, anchoring proteins, and signaling cascade components (Grunert and Wässle, 1993; Haase et al, 1990; Haverkamp and Wässle, 2000; Hu and Wensel, 2004; Krizaj and Copenhagen, 1998; Morgans et al, 1998; Ogata et al, 2012; Partida et al, 2004; Röhrenbeck et al, 1989; Ryskamp et al, 2011; Stahl and Baskin, 1984; Volgyi et al, 2005; Zucker, 1998); and markers that have been transported, gene-gunned, or transiently expressed (Coombs et al, 2006; Dacey et al, 2003; Morgan et al, 2006; Rockhill et al, 2002; Siegert et al, 2009; Stradleigh et al, 2015; Stradleigh et al, 2011). …”
Section: Formaldehydementioning
confidence: 99%
“…It has been possible to immunostain formaldehyde-fixed preparations with multiple primary antibodies (i.e., antibodies directed against more than one epitope) and thus test for colocalization of different antigens (Brandstätter et al, 2004; Li et al, 1986; Mills et al, 2001; Röhlich et al, 1994; Sassoe-Pognetto et al, 1995; Stradleigh et al, 2011), cell-specific expression (Hoshi et al, 2009; Lin and Masland, 2005; O'Brien et al, 2006; Rodriguez et al, 2014; Wässle et al, 2009), expression in identifiable subcellular compartments (Boiko et al, 2003; Greenberg et al, 2011; Jakobs et al, 2008; Rasband et al, 1999; Van Wart et al, 2007; Wu et al, 2013; Xu et al, 2008), and changes in the presence or localization of one antigen with opposite or no changes in another antigen (Elias et al, 2004; Ogata et al, 2012). Briefly stated, some of the most informative and aesthetically impressive images of immunostained retinae have been obtained with formaldehyde-fixed preparations that highlight specific populations of rods, cones (Bumsted and Hendrickson, 1999; Cuenca et al, 2014; Elias et al, 2004; Haverkamp et al, 2000; Haverkamp et al, 2005; Hornstein et al, 2004; Li and DeVries, 2004; O'Brien et al, 2012), bipolar cells (DeVries, 2000; Keeley and Reese, 2010; Kouyama and Marshak, 1992; Wässle et al, 2009; Young and Vaney, 1991), horizontal cells (Mills and Massey, 1994; O'Brien et al, 2006; Piccolino et al, 1984; Wässle et al, 2000), amacrine cells (Badea et al, 2009; Dacey, 1990; Lin and Masland, 2006; Lindstrom et al, 2009; Mills et al, 2001; Petrides and Trexler, 2008; Tauchi and Masland, 1984; Trexler et al, 2001; Voigt and Wässle, 1987), and ganglion cells (Coombs et al, 2006; Hattar et al, 2002; Jakobs et al, 2008; Kim et al, 2008; Nelson et al, 1978; O'Brien et al, 2002; Ogata et al, 2012; Rockhill et al, 2002; Van Wart et al, 2007; Vaney, 1991; Volgyi et al, 2005; Volgyi et...…”
Section: Formaldehydementioning
confidence: 99%